1962
DOI: 10.1038/193827a0
|View full text |Cite
|
Sign up to set email alerts
|

Mr. Charles S. Durst

Abstract: No. 4a1o March 3, 1962 NATURE 827 1\llagazine for the Society. In 1953 he was awarded the Veitch Memorial Gold Medal and in 1956 the Victoria Medal of Honour, the Society's highest award. He gained the O.B.E. in 1955. Until the last two years of his life Turrill belied his years both by his comparatively youthful appearance and by his activities. He was good-humoured and generous in helping those less gifted than himself. Recreation, apart from reading, seemed to come from change of work and his remarkably ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…19 A survey of practitioners in the United Kingdom found that the most commonly expressed concern detracting from DCC was maternal bleeding at cesarean section, especially with less experienced obstetricians. 20 Challenges to implementing DCC in the operating room have led to studies on comparing DCC with umbilical cord milking for infants born by cesarean delivery. One randomized controlled trial of two delivery centers found greater improvements in initial hemoglobin, systemic blood flow, blood pressure, and urine output at birth in premature infants delivered by cesarean who received umbilical cord milking compared with DCC for 45 to 60 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…19 A survey of practitioners in the United Kingdom found that the most commonly expressed concern detracting from DCC was maternal bleeding at cesarean section, especially with less experienced obstetricians. 20 Challenges to implementing DCC in the operating room have led to studies on comparing DCC with umbilical cord milking for infants born by cesarean delivery. One randomized controlled trial of two delivery centers found greater improvements in initial hemoglobin, systemic blood flow, blood pressure, and urine output at birth in premature infants delivered by cesarean who received umbilical cord milking compared with DCC for 45 to 60 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, this may be the reason why CS deliveries are less likely to have DCC performed compared with vaginal deliveries. 14,22 Therefore, UCM appears to be a more feasible and efficient alternative to DCC during CS because it takes less than 30 seconds to perform. 23 However, UCM is not widely practiced probably due to a limited number of studies establishing benefits in term infants and the concern for short-term adverse effects of increased blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of mounting evidence that a delay in clamping of the umbilical cord is beneficial for preterm neonates, 9,10,18 many centers continue to practice immediate cord clamping to avoid a delay in resuscitation, particularly for infants who are not vigorous at birth. 19,20 Two studies of preterm infants who underwent DCC demonstrated that those who do not breathe before the cord is clamped have worse outcomes, 21,22 and evidence from preclinical models suggest that lung inflation prior to cord clamping is critical for reducing swings in cerebral and systemic blood pressure that could lead to ischemia or hemorrhage. 13,14 In our small pilot study of 29 infants, we found that assisting ventilation of very preterm infants < 33 weeks' gestation while attached to the placenta is feasible and safe.…”
Section: Discussionmentioning
confidence: 99%